2011
DOI: 10.5194/acp-11-6115-2011
|View full text |Cite
|
Sign up to set email alerts
|

Jet characterization in the upper troposphere/lower stratosphere (UTLS): applications to climatology and transport studies

Abstract: A method of classifying the upper tropospheric/lower stratospheric (UTLS) jets has been developed that allows satellite and aircraft trace gas data and meteorological fields to be efficiently mapped in a jet coordinate view. A detailed characterization of multiple tropopauses accompanies the jet characterization. Jet climatologies show the well-known high altitude subtropical and lower altitude polar jets in the upper troposphere, as well as a pattern of concentric polar and subtropical jets in the Southern He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
160
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 91 publications
(170 citation statements)
references
References 75 publications
10
160
0
Order By: Relevance
“…Figure 6 shows integrated losses for each of the Arctic and Antarctic winters observed by MLS through March 2013. As expected (e.g., Manney et al, 2011;World Meteorological Organization, 2014), Arctic ozone loss is by far the greatest in the 2010/11 winter, with 2 ppmv loss estimated at 450 K (the 26 March end date for this estimate was necessitated by an anomalous temporary shutdown of the MLS instrument; normal operations resumed on 19 April 2011). Consistent with our comparisons for the 2004/05 winter, this estimate is in reasonable agreement with those from other studies, though on the low side.…”
Section: Comparison To Previous Estimates Of Ozone Loss In Thesupporting
confidence: 70%
See 2 more Smart Citations
“…Figure 6 shows integrated losses for each of the Arctic and Antarctic winters observed by MLS through March 2013. As expected (e.g., Manney et al, 2011;World Meteorological Organization, 2014), Arctic ozone loss is by far the greatest in the 2010/11 winter, with 2 ppmv loss estimated at 450 K (the 26 March end date for this estimate was necessitated by an anomalous temporary shutdown of the MLS instrument; normal operations resumed on 19 April 2011). Consistent with our comparisons for the 2004/05 winter, this estimate is in reasonable agreement with those from other studies, though on the low side.…”
Section: Comparison To Previous Estimates Of Ozone Loss In Thesupporting
confidence: 70%
“…Consistent with our comparisons for the 2004/05 winter, this estimate is in reasonable agreement with those from other studies, though on the low side. Manney et al (2011) estimate ∼ 2.5 ppmv of loss at 450 K based on both MLS and ozonesonde observations, while Kuttippurath et al (2012) estimate ∼ 2.5 ppmv loss at 475 K (∼ 19 km) using subtraction of passive ozone (derived by the "Mimosa-Chim" model) from MLS observations. Sinnhuber et al (2011) The 2005/06, 2008/09, 2011/12, and 2012/13 Arctic winters have the smallest losses, in many cases indistinguishable from zero when possible transport errors are factored in.…”
Section: Comparison To Previous Estimates Of Ozone Loss In Thementioning
confidence: 99%
See 1 more Smart Citation
“…If dT /dz drops below −2 K km −1 above the primary thermal tropopause, then the next level above that where the WMO criterion is fulfilled is identified as a multiple tropopause (e.g., Randel et al, 2007;Manney et al, 2011Manney et al, , 2014; this definition follows that of Randel et al (2007), who showed that requiring dT /dz to drop only below −2 K km −1 above the primary tropopause for the relatively coarse resolution reanalyses (rather than −3 K km −1 as is typically used for high-resolution temperature profiles) resulted in multiple tropopause distributions more comparable to those from high-resolution measurements. Linear interpolation is used to locate the tropopause between two adjacent vertical grid points.…”
Section: Jet and Tropopause Characterizationmentioning
confidence: 99%
“…While Davis and Birner (2017) used four of the five modern reanalyses we will compare here, their tropopause and jet-based tropical width diagnostics were based on analysis of zonal mean fields. Manney et al (2011) developed a method for characterizing the upper tropospheric jets, the stratospheric subvortex jet, and multiple tropopauses. Manney et al (2014) used this package to present a detailed climatology of these UTLS jets and multiple tropopauses, and the relationships between them, using GMAO's Modern-Era Retrospective analysis for Research and Applications (MERRA).…”
Section: Introductionmentioning
confidence: 99%